Comparison of DECAF (dyspnea, eosinopenia, consolidation, acidaemia, and atrial fibrillation) and APACHE II (acute physiology and chronic health evaluation ii) scoring system to predict mortality among patients with acute exacerbation of chronic obstructive pulmonary disease - Wiky Raja; Naseem Ahmed; Nadeem Ahmed Rizvi; Anita Vallacha; Dinesh Kumar (Journal of the Pakistan Medical Association, 2021)
Scoring systems are frequently used to predict mortality and then guiding therapeutic interventions in the patients with acute exacerbation of chronic obstructive pulmonary disease. Objective: Compare the diagnostic accuracy of Dyspnea, Eosinopenia, Consolidation, acidaemia, and atrial fibrillation and acute physiology and chronic health evaluation II scoring system to predict mortality among patients with acute exacerbation of chronic obstructive pulmonary disease. Methods: A cross sectional study was conducted during November 2017 to June 2018 in the Department of Chest Medicine, Jinnah Postgraduate Medical Center, Karachi. N=210 patients with acute exacerbation of chronic obstructive pulmonary disease, were included in the study after getting written informed consent. Patients were selected using non-probability consecutive sampling technique. Mortality scores were calculated for each patient and the individual parameters used in calculating the scores were also recorded. SPSS version 21 was used for statistical analysis. Results: The study population consisted of 210 consecutive patients, of those n=147 (70%) were males and n= 63 (30%) females. A statistically significant difference was observed between survivors and those who died in hospital related to acute exacerbation of chronic obstructive disease. The mean Dyspnea, Eosinopenia, Consolidation, acidaemia, and atrial fibrillation score 2.31 + 0.93 and acute physiology and chronic health evaluation II score 15.8 + 7.2 was recorded in whole study population. A decision threshold of Dyspnea, Eosinopenia, Consolidation, acidaemia, and atrial fibrillation score >2 was found to have a sensitivity of 84.6% and specificity of 82.3% while acute physiology and chronic health evaluation II score have sensitivity Continuous...